A BIODEGRADABLE FILM FROM JACKFRUIT (ARTOCARPUS HETEROPHYLLUS) AND DURIAN (DURIO ZIBETHINUS) SEED FLOURS - Diah S. Retnowati; Ratnawati Ratnawati; Aprilina Purbasari (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The jackfruit (Artocarpus heterophyllus) and durian (Durio zibethinus) seeds contain high portion of amylose, which makes them potential materials for biodegradable films. The objective of this study is to develop biodegradable films composed of jackfruit and durian seed flours and glycerol as plasticizer. The films were prepared by dispersing flours in water, adding glycerol, heating the mixture, casting the solution on an acrylic plate, and drying the films at 50 ºC for 20 hours. Glycerol contributes to the flexibility of the film, while reduces the strength of the film. The Young’s modulus, tensile strength, and elongation at break increase as the ratio of jackfruit to durian seed flour increases. The films made from jackfruit and durian seed flours in this work are stronger than the film made from rice flour obtained by other researcher. Therefore, jackfruit and durian seed flours are potential raw material for biodegradable films.